2015
DOI: 10.3389/fpsyt.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sleep in Military Personnel is Associated with Changes in the Expression of Inflammatory Genes and Improvement in Depression Symptoms

Abstract: Study objectivesSleep disturbances are common in military personnel and are associated with increased risk for psychiatric morbidity, including posttraumatic stress disorder (PTSD) and depression, as well as inflammation. Improved sleep quality is linked to reductions in inflammatory bio-markers; however, the underlying mechanisms remain elusive.MethodsIn this study, we examine whole genome expression changes related to improved sleep in 68 military personnel diagnosed with insomnia. Subjects were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…One gene in particular, Urotensin 2, was significantly down regulated, and represents a potential insomnia target, given its role in orexin regulation and rapid eye movement. Another study by the same group investigated gene expression changes in military personnel with insomnia, focusing on differences between individuals who did or did not experience improvements in sleep following three months of insomnia treatment [94]. Positive changes in immune-related genes (i.e., lower expression of inflammatory cytokines, increases in regulatory genes), implication of the ubiquitin pathway (via pathway analysis) and improvement in depression symptoms were all seen in the improved sleep group, providing insight into the molecular changes that occur with successful insomnia interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One gene in particular, Urotensin 2, was significantly down regulated, and represents a potential insomnia target, given its role in orexin regulation and rapid eye movement. Another study by the same group investigated gene expression changes in military personnel with insomnia, focusing on differences between individuals who did or did not experience improvements in sleep following three months of insomnia treatment [94]. Positive changes in immune-related genes (i.e., lower expression of inflammatory cytokines, increases in regulatory genes), implication of the ubiquitin pathway (via pathway analysis) and improvement in depression symptoms were all seen in the improved sleep group, providing insight into the molecular changes that occur with successful insomnia interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Partitioning of heritability across tissue types 25,26 showed enrichment in the central nervous system, adrenal/pancreas tissue lineages and skeletal muscle (p<10 -5 ) (Supplementary Table 17 [29][30][31][32] . Furthermore, the restless legs syndrome gene BTBD9 has been implicated as a substrate adaptor for the Cullin-3 class of E3 ubiquitin ligases 33 .…”
mentioning
confidence: 99%
“…This gene has been associated with switching between different stages of sleep, which may in turn be the mechanism underlying insomnia symptoms (Gill, et al, 2015). Further, in another study, Dr. Gill’s team found that for patients whose sleep improved, inflammatory genes were expressed differently compared to their own baseline expression, and, that the differential expression was also related to reductions in depression symptoms (Livingston, et al, 2015). These studies show that differential gene-expression relates to insomnia and chronic symptoms in military personnel, and that standard care can change gene-activity.…”
Section: Complex Symptoms Of Neurological Traumamentioning
confidence: 99%